A Study of Light Intensity and Fertilizer on Soybean in Albizia chinensis Agroforestry System - Zulfikar Affandi; Djoko Purnomo; Supriyono Supriyono (SAINS TANAH - Journal of Soil Science and Agroclimatology, 2019)
One of the efforts to solve the decreasing of agriculture land area caused by land use change is through agroforestry system (AF), such as the cultivation among the Albizia chinensis trees. This research, along with the experiment, aims at studying the light characteristic of 1.5 years oldAlbizia c and the effect of fertilization on the growth of soybean and testing the soybean yield of Dega 1 varieties in agroforestry system based on Albizia c. Using the split-plot Randomized Block Design (RBD) as the experiment, the intensity of light was employed as the main plot whereas the fertilizer was used as the subplot in this study. There were four levels of light intensity:  land with high light intensity (lands outside AF), rather high light intensity (radiation transmission fraction (RTF) among Albizia c 1425 ha-1 density), medium-high light intensity (RTF among 2850 Albizia c density with pruned canopy), rather low light intensity (RTF among 2850 Albizia c  density with unpruned canopy). As the subplot were some various fertilizers such as Albizia c litter, Albizia c litter + phosphorus (P) + potassium (K), and without any fertilization. Totally 12 treatments were obtained and each of those treatments was replicated three times, consequently consisting of 36 experiment units. The result of this research shows that  Albizia c was exceedingly potential for the soybean cultivation with AF system. The passing light under the canopy (RTF) depended on the distance between each tree and could be improved by pruning the canopy. The increasing RTF increased vegetative and generative growth. The highest soybean production (3.3 tons ha-1) could be achieved in 2850 trees ha-1 density with pruned canopy (RTF: 49% equals to 28440 lux) compared with biomass production in open land (3.9 tons ha-1).